Development and psychometric testing of the FLW-MSC scale for measuring frontline worker multisectoral collaboration in rural India. Issue 3 (4th March 2021) - Glandon, Douglas; Leoutsakos, Jeannie-Marie; Gupta, Shivam; Marsteller, Jill; Paina, Ligia; Bennett, Sara
Abstract : Objectives: Multisectoral collaboration (MSC) is widely recognised as a critical aspect of policies, programmes and interventions addressing complex public health issues, yet it is undertheorised and difficult to measure. Limited understanding of the intermediate steps linking MSC formation to intended health outcomes leaves a substantial knowledge gap about the types of strategies that may be most effective in making such collaborations successful. This paper, which reports the quantitative strand of a broader mixed-methods study, takes a step toward filling in this 'missing middle' of MSC evaluation by developing and testing the FLW-MSC scale, an instrument to assess collaboration among the frontline workers of one of India's largest and most widely known MSCs: the Integrated Child Development Services (ICDS) scheme. Design: This study involved development, field-testing and psychometric testing of an 18-item, Likert-type frontline worker collaboration scale, including internal consistency, construct validity and criterion validity. Setting: Village-level primary healthcare in rural Uttar Pradesh, India. Participants: 281 anganwadi workers, 266 accredited social health activists and 124 auxiliary nurse midwives selected based on random sampling of anganwadi catchment areas from 346 gram panchayats (GPs), including 173 intervention GPs and 173 pair-matched control GPs from a parent evaluation study. Results: Results support the scale's internal consistency (ordinal α=0.92–0.95), construct validity (reasonable exploratory factor analysis model fit for five of the six dyadic relationships Tucker-Lewis Index=0.84–0.88; Root Mean Squared Error of Approximation=0.09–0.11), and criterion validity (regression of collaboration score on an information-sharing indicator β=3.528; p=0.006). Conclusions: The scale may be useful for ICDS managers to detect and address poor collaboration as the Indian government redoubles its efforts to strengthen and monitor MSC, or 'convergence', with important implications for the critical priority of child development. Further, the FLW-MSC scale may be adapted for measuring frontline worker collaboration across sectors in many other scenarios and low/middle-income country contexts.